Manajemen Budaya Religius Berbasis Pembiasaan Dalam Meningkatkan Mutu Pendidikan Di Smp Muhammadiyah 1 Berbah - Fabroy Fauziyatul Munawwaroh (Universitas Pakuan, 2026)
HABIT-BASED RELIGIOUS CULTURE MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION AT MUHAMMADIYAH 1 BERBAH MIDDLE SCHOOL This study aims to describe habit-based religious culture management and its contribution to improving the quality of education at SMP Muhammadiyah 1 Berbah. The study used a qualitative approach with field research. Data were obtained through interviews, observation, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawing. Data validity was carried out through triangulation of sources and techniques. The results of the study indicate that habit-based religious culture management is carried out through planning, organizing, implementing, and evaluating functions. Program implementation is carried out through greetings, smiles, and greetings, dhuha prayers and short sermons, Al-Qur'an recitation, congregational dhuhur prayers, and female studies. Evaluation is carried out continuously through supervision and guidance by teachers and the principal. Habitual-based religious culture contributes to improving the quality of education by strengthening religious character, increasing discipline and responsibility, developing leadership and self-confidence, and creating a religious and conducive school environment. This study concludes that habit-based religious culture is an effective management strategy in supporting the improvement of the quality of education holistically.